MGA TURA: A LITERARY ANALYSIS OF MANSAKA POEMS - Krystal Joy M. Clamares, PhD, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The purpose of this undertaking was to illuminate the literary analysis of poetry as perceived in Mansaka context at Maragusan, Compostela Valley Province. Phenomenological approach was employed to highlight the culture, tradition and practices of the participants. This study aimed to develop and gather deep information through inductive and qualitative method such as interviews and discussions. Further, it involved 14 Mansaka respondents in the Municipality of Maragusan, Compostela Valley Province. Through the employed in- depth interviews and focus group discussion, it was revealed that the poems of Mansaka have different literary features like theme, tone, rhyme scheme, simile, hyperbole, repetitions, assonance, consonance and alliteration and was only limited with these salient features. The findings also revealed that the oral traditions of the elders, educating the young generations and highlighted during rituals played a great role in preserving their poetry. Finally, the different insights of Mansaka tribesmen revealed the importance of positive impact of technology, academic integration, support from the government, roles of young generations in preservation and poetry showcasing tradition. Hence, this study will be resonated in the academe and opens a profound significance on appreciating the literary pieces of Mansaka.